2009
DOI: 10.1111/j.1743-6109.2008.01171.x
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of and Risk Factors for Androgen Deficiency in Aging Taiwanese Men

Abstract: Introduction Androgen deficiency in aging men has attracted much medical interest. Most studies on androgen deficiency have been conducted in Caucasian populations, and data from other ethnicities are lacking. Aim To evaluate the prevalence of and risk factors for androgen deficiency and symptomatic androgen deficiency in Taiwanese men over 40 years old. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
74
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 59 publications
1
74
1
Order By: Relevance
“…Reported effect measures were primarily ORs or correlation coefficients and low T was defined using various thresholds of TT or free testosterone (FT), and quartile or tertile comparisons. Increasing age (Smith et al, 2000;Blouin et al, 2005;Hall et al, 2008a,b;Dhindsa et al, 2010;Tajar et al, 2012) (Liu et al, 2009) (Blouin et al, 2005;Svartberg et al, 2006;Hall et al, 2008a,b), and poor health status (Mulligan et al, 2006;Hall et al, 2008a,b;Liu et al, 2009;Schneider et al, 2009;Tajar et al, 2012) were consistently found to be significantly associated with hypogonadism in all of the population and primary care-based cross-sectional studies in which they were assessed. Metabolic syndrome was significantly associated to hypogonadism in three population-based studies (Blouin et al, 2005;Svartberg et al, 2006;Tajar et al, 2012) and in one primary care study (Schneider et al, 2009), although it did not remain an independent comorbidity on multivariate analysis in one of the population-based studies (Tajar et al, 2012).…”
Section: Comorbiditiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Reported effect measures were primarily ORs or correlation coefficients and low T was defined using various thresholds of TT or free testosterone (FT), and quartile or tertile comparisons. Increasing age (Smith et al, 2000;Blouin et al, 2005;Hall et al, 2008a,b;Dhindsa et al, 2010;Tajar et al, 2012) (Liu et al, 2009) (Blouin et al, 2005;Svartberg et al, 2006;Hall et al, 2008a,b), and poor health status (Mulligan et al, 2006;Hall et al, 2008a,b;Liu et al, 2009;Schneider et al, 2009;Tajar et al, 2012) were consistently found to be significantly associated with hypogonadism in all of the population and primary care-based cross-sectional studies in which they were assessed. Metabolic syndrome was significantly associated to hypogonadism in three population-based studies (Blouin et al, 2005;Svartberg et al, 2006;Tajar et al, 2012) and in one primary care study (Schneider et al, 2009), although it did not remain an independent comorbidity on multivariate analysis in one of the population-based studies (Tajar et al, 2012).…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Diabetes mellitus was significantly associated with hypogonadism in three (Smith et al, 2000;Selvin et al, 2007;Tajar et al, 2012) of the five (Smith et al, 2000;Wong et al, 2006;Selvin et al, 2007;Hall et al, 2008a,b;Tajar et al, 2012) populationbased studies and in all three of the primary care studies, in which it was assessed (Mulligan et al, 2006;Liu et al, 2009;Dhindsa et al, 2010). Among the three population-based studies, DM was related to severe (TT < 8 nmol/L) but not moderate hypogonadism (TT of 8-11 nmol/L) in one study (Tajar et al, 2012), and to FT but not TT in another study (Selvin et al, 2007).…”
Section: Comorbiditiesmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Indeed, despite the lack of precise criteria for andropause, 26 both crosssectional and longitudinal studies have estimated that a substantial number of older men (i.e., especially aged ‡ 70 years) may have low sex steroid hormone levels. 8,10,[41][42][43][44][45][46][47][48][49] This condition places them at higher risk for adverse health outcomes and premature death. 8,28,[50][51][52][53][54][55] This review will aim to examine the uncertainty regarding the nature and the clinical importance of the age-related reduction in the T levels.…”
Section: Introductionmentioning
confidence: 99%
“…While a medical history of orchitis, testicular trauma, or other pathology may be contributory, 57 interestingly, increased adiposity and obesity were strongly associated with lower TT, FT, and SHBG levels in middle-aged and older men. 57,79,87,[151][152][153][154] Similarly diabetes mellitus and insulin concentrations have been found to be indirectly correlated with SHBG and TT concentrations. 155,156 With respect to lifestyle, excess intake of alcohol and physical and psychological stress were also associated with lower TT concentrations.…”
mentioning
confidence: 98%